Generalized factorized groups with dispersible subgroups - Verpatova, N. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We generalize the well-known nition of complementability of subgroups. We describe the structure of nondispersible generalized factorized groups all subgroups of which are dispersible.